Individual and Regional Christian Religion and the Consideration of Sustainable Criteria in Consumption and Investment Decisions: An Exploratory Econometric Analysis - Gutsche, Gunnar (Journal of business ethics, 2019)
This study aims to shed light on the relationship between individual and regional Christian religion (and religiosity) and individual sustainable behaviors in an exploratory manner, with a special focus on sustainable consumption and investment decisions. To this end, we econometrically analyze online representative survey data that contains information on the self-reported importance of the consideration of ecological and social/ethical criteria in the context of a large variety of individual behaviors. The target group are financial decisions makers in German households, i.e., important actors in the largest economy in Europe. Results of the econometric analysis suggest that Christian religion is positively related to a variety of (self-reported) ecological and social/ethical activities. Our findings empirically support explanations postulating a positive relationship between Christian religion and environmental behavior, such as the stewardship hypothesis, rather than opposite theories like White’s (Science 155(3767):1203–1207, 1967) dominion hypothesis. Particularly, we find that both individual and regional measures for Christian religion positively affect various behaviors emphasizing the importance of individual and contextual norms for individual behavior. Hence, we provide empirical evidence for the importance of Christian religion for another country than the USA, which is typically in the focus of similar studies. Our results can be used for targeted information campaigns by politicians to enhance sustainable behaviors or acceptance for related policy measures.